THE COHESIVE DEVICES OF STUDENTS’ WRITING RECOUNT TEXT - Maulidina Bunga Halimatusyahdiah; Siti Aisah Ginting (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2022)
The aims of the study were to discover the kinds of cohesive devices that were used in students’ writing recount text, to investigate the contribution of cohesive devices in students’ recount text, and to find out the reasons why students used cohesive devices. The study used the frameworks of Halliday&Hasan (1976) and Eggins (2004). The study used descriptive qualitative research. The data was analyzed based on Miles, Huberman, and Saldana’s (2014) framework. The results of the findings revealed that students in Grade X at SMA Negeri 15 Medan used four cohesive devices, namely reference, substitution, ellipsis and conjunction. There was 58,97% contribution of lexical cohesion, which was indicated through the use of vocabulary of nouns and verbs, followed by reference that had 30,69% contribution. It was derived from category of person as well as the scale of proximity. Conjunction, on the other hand, had the percentage as much as 10,34% which was obtained through extension and enhancement type. Furthermore, the findings of the study found 8 out of 12 reasons why students used cohesive devices.Keywords: Cohesive Devices, Students’ Writing, Recount Text